FOMO IN THE PERSPECTIVE OF THE QUR’AN: A THEMATIC STUDY ON PEACE OF MIND AND SIMPLICITY OF LIFE - Selamet Riadi; Abdul Wahab; Citra Lestari (Sekolah Tinggi Agama Islam Sadra, 2025)
The phenomenon of FOMO (Fear of Missing Out), or the fear of missing out on certain trends, events, or social experiences, has become a common psychological symptom in the digital age. The constant anxiety to participate in the lives of others as portrayed on social media often causes restlessness, dissatisfaction, and even identity crises. The Qur’an, as a guide for Muslims, provides many verses that can be used as references to overcome such anxiety, especially through the concepts of peace of mind (sakīnah) and simplicity of life (qanā‘ah). This study aims to explore how the Qur’an offers a perspective on FOMO by analyzing verses related to inner peace and simplicity in life, in overcoming FOMO, such as Q.S. Al-Baqarah [2]: 155, Q.S. An-Nisā’ [4]: 32, Q.S. An-Nisā’ [4]: 83, and Q.S. Al-Ḥadīd [57]: 20. This study uses a library research-based method with a thematic (mawḍū‘ī) approach, which organizes and analyzes verses of the Qur’an based on theme. The main sources are the Qur’an and Tafsīr al-Taḥrīr wa al-Tanwīr by Ibn ‘Āshūr (1879–1973), a prominent Tunisian scholar known for his contextual tafsir methodology, supplemented by contemporary psychological studies. The findings show that the Qur’an promotes tranquility through faith in Allah, dependence (tawakkul), contentment (qanā‘ah), and awareness of the temporary nature of worldly life. These teachings provide a spiritual framework for combating FOMO by fostering self-awareness and a deeper meaning of life. Therefore, the values of the Qur’an can be considered a spiritual remedy for modern social anxieties such as FOMO.